POSBank - DBS bank merger and its impact on POSBank customers - Chong, Shu Yee. (2008)
The purpose of this research study is to identify POSBank customers’ fears and concerns of the POSBank – DBS Bank merger, determine customers’ reactions to the merger and identify the factors that affect customers’ decision to continue banking relationship with POSBank. The dependent variable for this research study is customers’ decision to continue banking relationship with POSBank.